Numerical simulations on optical pulse propagation and amplification in single mode fibers - Chong, Li Yang (2019)
Optical solitons are optical field that does not alter its shape during propagation regardless of the transmission distance and materials. This phenomenon is made possible through the balancing of dispersive and nonlinear effects in the transmitting medium. In this final year project, an interface/ application will be formulated to conduct simulation and capture the output of the system to have a better understanding of this phenomenon. This report will discuss the theoretical part of the dispersive and nonlinear effects as well as a guide to formulate the application and finally the results obtained from the simulation.